The sugar ring of the nucleoside is required for productive substrate positioning in the active site of human deoxycytidine kinase (dCK): implications for the development of dCK-activated acyclic guanine analogs - Hazra, Saugata (2010)
The low toxicity of acyclovir (ACV) is mainly due to the fact that human nucleoside kinases have undetectable phosphorylation rates with this acyclic guanine analog. In contrast, herpes virus thymidine kinase (HSV1-TK) readily activates ACV. We wanted to understand why human deoxycytidine kinase (dCK), which is related to HSV1-TK and phosphorylates deoxyguanosine, does not accept acyclic guanine analogs as substrates. Therefore, we crystallized dCK in complex with ACV at the nucleoside phosphoryl acceptor site, and UDP at the phosphoryl donor site. The structure reveals that while ACV does bind at the dCK active site, it does so adopting a non-productive conformation. Despite binding ACV, the enzyme remains in the open, inactive state. In comparison to ACV binding to HSV1-TK, in dCK the nucleoside base adopts a different orientation related by about a 60 degree rotation. Our analysis suggests that dCK would phosphorylate acyclic guanine analogs if they can induce a similar rotation.